Resource characteristics and stock assessment of lesser sardines in the Indian waters - Bennet, P Sam; Nair, P N Radhakrishnan; Luther, G; Annigeri, G G; Sreenivasarangan, S; Kurup, K N (Indian Journal of Fisheries, 2011)
The fishery and biology of commercially important species of lesser sardine resources of India werestudied. Detailed gearwise, specieswise and monthwise landings for 1984-88 are presented. In Goa-Kamatakaregion the main gear was purse seine, whereas in the Kerala region it was gill net. On the east coast, Tamil NaduPondicherryrecorded maximum landings through gill nets and Andhra-Orissa through boat seines and gill nets.Sardinella gibbosa was the important species in the west and southeast coasts of India, and S . .fimbriata in thenortheast region. Growth parameters for different species were estimated. Stock assessment for S. gibbo.v showed that the fish is optimally exploited in the Tamil Nadu-Pondicherry region, whereas in the west coast(Kerala and Goa- Kamataka regions) the fishery can be improved with additional effort. In the Andhra-Orissaregion, the effort is beyond the MSY level.